The Improvement of Energy Concept Understanding of Students with Deaf in Special Needs Junior High Schools Using Energy Change Props - Rusilowati, Ani; Hidayah, Isti; Ellianawati, Ellianawati; Setiani, Yuniar (International Journal of Research Innovation and Entrepreneurship, 2020)
The learning process of deaf students requires more time than that of normal students. This also occurred in physics topics of natural science subject. In order to support the deaf students’ concept understanding, learning media such as teaching props, are needed. This support would help them to maximize their senses of sight and touch. This study aims to determine the effectiveness of energy change props in enhancing energy concept understanding for deaf students. This research was a quasi-experimental study with a single subject research design. The subjects of the study were five deaf students of grade VII in a junior school for special-needs students in Central Java, Indonesia. The effectiveness of learning has been shown from the improvement of conceptualization from base-line condition to intervention. An effect size technique was used in the data analysis. The result showed that the obtained average effect size in this study was 1.32 with a high category. This study indicated that the props for energy change were effective for enhancing energy concept understanding for deaf students.